Triaina, a new genus in the Janirellidae Menzies, 1956 (Crustacea: Isopoda: Asellota), with two new species from south-eastern Australia, and a new diagnosis for the family - Just, Jean (Zootaxa, 2009)
The varying concepts of Janirellidae Menzies, 1956 are outlined, including its rejection by several authors. The view of Wilson and Wägele of Janirellidae being a valid family comprising Janirella Bonnier, 1896 and presumably Dactylostylis Richardson, 1911 (= Spinianirella Menzies, 1962) is accepted. Diagnoses of the Janirellidae subsequent to Menzies’ original one were based on the inclusion of a diverse range of genera now recognised as not belonging in that family. A new diagnosis of Janirellidae is presented based on the inclusion of Janirella, Dactylostylis, and a new genus Triaina with two new species, T. isodonte and T. makridonte, from south-eastern Australia. The latter species represents the shallowest record (80 m) of the otherwise predominantly deep-water family. All species in the family are listed in an appendix, with area of type locality and depth range.